Comparison of Suppressive Antibiotics for Prevention of Recurrent Urinary Tract Infection in Adult Females - Usman, Rida; Rauf , Abdul; Khan, Fazal Ur Rehman; Fateh, Umer; Abbas, Muhammad Tahir; Khan, Muhammad Jaleed (Biological and Clinical Sciences Research Journal, 2025)
Urinary tract infections (UTIs) are among the most common bacterial infections in women, with a significant proportion experiencing recurrent UTIs (rUTIs). Due to Pakistan’s rising antimicrobial resistance (AMR) rates, selecting effective prophylactic antibiotic therapy is crucial. Fosfomycin and nitrofurantoin are widely recommended first-line treatments, but their comparative efficacy in the Pakistani population remains underexplored. Objective: To compare the efficacy of fosfomycin and nitrofurantoin in preventing rUTIs among female patients and to identify risk factors associated with UTI recurrence in the Pakistani population. Methods: This randomised controlled trial was conducted from 29 October 2024 to 29 January 2025 at the Department of Urology, Shaikh Zayed Hospital, Lahore.. A total of 200 female patients with a history of rUTIs were randomly assigned to receive either fosfomycin (3g once every 10 days) or nitrofurantoin (100mg daily at bedtime). Patients were followed up at six weeks and three months, and recurrence was assessed based on clinical symptoms and urine culture analysis. Data analysis was performed using SPSS version 25, with statistical significance set at p ≤ 0.05. Results: At six weeks, recurrence rates were significantly lower in the fosfomycin group (15%) compared to the nitrofurantoin group (30%) (p = 0.012). At three months, 25% of patients on fosfomycin and 40% on nitrofurantoin experienced recurrence (p = 0.018). Diabetic patients had significantly higher recurrence rates (60%) compared to non-diabetics (25%) (p < 0.001). Additionally, obese patients exhibited higher recurrence rates (50%) than those with normal BMI (20%) (p = 0.025). Conclusion: The study demonstrates that fosfomycin is more effective than nitrofurantoin in preventing rUTIs in Pakistani women. Diabetes and obesity were identified as significant risk factors for recurrence. These findings underscore the need for tailored prophylactic strategies and antibiotic stewardship programs in Pakistan. Further long-term, multicenter studies are recommended to refine national guidelines for UTI management.